Ethnobotanical Study of Medicinal and Spices Plants in Long Nawang Village, Kayan Hulu District - Listiani Listiani; Mari Ingan; Jaka Hadi Jaya (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
Ethnobotanical research of the people of Long Nawang Village is aimed at uncovering local knowledge of the community in utilizing plants as medicine and spices. This is qualitative research that uses interviews and documentation to collect data. Data was collected in Long Nawang Village, Kayan Hulu District, Malinau Regency. There were five respondents selected as the participants for this study. The results showed that 16 Families and 22 plant species are used by the Dayak Kenyah ethnicity in Long Nawang. The plant organs most widely used as medicine are fruit organs, such as rhizomes, leaves, stems, and roots. To use the plants for medicines, the local people mostly boiled or consumed directly the parts of the plants. While for the spices, the most widely used ingredients are rhizomes, and the fewest are tubers, seeds, and leaves